2015
DOI: 10.1353/rhe.2015.0014
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gender and Race Intersectionality on Student Learning Outcomes In Engineering

Abstract: Women and underrepresented minorities in traditionally White and male-dominated disciplines tend to report lower learning outcomes than their White peers. Adopting a feminist intersectionality framework, this study looks at the intersections of gender and race to investigate differences in self-assessed learning outcomes in engineering undergraduate education. We found that Black women, Asian men, and men from Other racial/ethnic groups tend to rate their skills lower than their White counterparts. We suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 67 publications
2
73
1
2
Order By: Relevance
“…Interestingly, black and Hispanic students were neither more nor less likely than white students to graduate with a STEM degree, but Asian students were 12% more likely. Consistent with previous research, we find that female students were less likely than male students to get a STEM degree (see Ro & Loya, 2015).…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, black and Hispanic students were neither more nor less likely than white students to graduate with a STEM degree, but Asian students were 12% more likely. Consistent with previous research, we find that female students were less likely than male students to get a STEM degree (see Ro & Loya, 2015).…”
Section: Resultssupporting
confidence: 92%
“…The largest variation is seen in Teamwork, where females tend to have a higher confidence in their teamwork skills. This is consistent with other research that has shown women typically assess their professional skills, including teamwork, higher than men 14 . Considering the small sample size, further data will need to be collected to provide a stronger understanding of the difference within the context of this research.…”
Section: Gender Perspectives On Engineering Leadershipsupporting
confidence: 92%
“…Institutional researchers have the opportunity of gathering both quantitative and qualitative data on their own campuses and can play an important role in helping faculty, staff and administrators design and implement programs and policies that can make a meaningful difference in diversifying STEM within their campus community. Overall, it is important to also encourage policies and practices that are aimed at bolstering professional self‐confidence and sense of belonging and community, as well as access and persistence in STEM for women (e.g., Marra, Rodgers, Shen, & Bogue, ; Ro & Loya, ). The practices and examples presented in this chapter provide ways in which educational environments, policies, and practices can be successful in supporting a sense of belonging and a sense of community that will be more attractive for all students, in particular women, enrolled in engineering programs.…”
Section: Conclusion and Implications For Institutional Researchersmentioning
confidence: 99%
“…This chapter' s use of this framework focuses mostly on institutional and school/department context because of the potential for influencing the recruitment and retention of female engineers, and faculty members and administrators, including institutional researchers, are more likely to control and/or change organizational features. This framework has been utilized in other research involving engineering, such as recruitment (e.g., Knight, Trautvetter & Novoselich, 2014) and the effect of gender and race intersectionality on student learning outcomes (Ro & Loya, 2015). Many recent studies involving STEM-including engineeringsurface from National Science Foundation (NSF) and Department of Education initiatives such as ADVANCE, IGERT, NRT, and INCLUDES.…”
Section: Lois Calian Trautvettermentioning
confidence: 99%